Fatores de correção do perímetro escrotal para efeitos de idade e peso ao sobreano de tourinhos nelore - Dal-Farra, Rossano André; Fries, Luiz Alberto [UNESP]; Lobato, José Fernando Piva (My University, 1998)
The aim of the study was to estimate adjustment factors to be used in genetic selection programs. Measurement data of scrotal circumference Nellore breed bulls from different herds raised on Brazilian tropical pasture conditions, totalizing 8934 animals of the 346 contemporary groups (CG) were analyzed. The means and standard deviations of real scrotal circumference (PEREAL), age at yearling weight (ISOB) and yearling weight adjusted to 550 days (PPD550), and age-of-dam were, respectively: 28.44 ± 3.35 cm; 589.04 ± 42.66 days; 333.03 ± 36.25 kg and 5.84 ± 3.01 years. The segmented polynomials (Spline functions) were used to estimate the adjustment factors for age and yearling weight, being used 550 days and 330 kg for age and weight, respectively, as standard values. Anticipation scrotal circumference measurements for 520-550 days could increase the selection efficiency for sexual precocity.
Adjustment factors of scrotal circumference for age and yearling weight effects of young nelore bulls
Keywords: Scrotal circumference to weight ratio; Segmented polynomials; Sexual precocity; Spline functions; Animalia